Automorphisms of a finitary factor power of an infinite symmetric group
We consider a semigroup FP^+_fin (S_fin (N)) defined as a finitary factor power of a finitary symmetric group of countable order. It is proved that all automorphisms of FP^+_fin (S_fin (N)) are induced by permutations from S_fin (N)., number=7, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Hudzenko, S. V., year=2010, month=Jul., pages=997–1001